A First for Human Vaccinology: GMP Compliant Radiation Attenuation of Plasmodium falciparum Sporozoites for Production of a Vaccine Against Malaria - James, Eric R.; Matheny, Steve; Overby, James; Sim, B. Kim Lee; Eappen, Abraham G.; Li, Tao; Li, Ming Lin; Richie, Thomas L.; Chakravarty, Sumana; Gunasekera, Anusha; Murshedkar, Tooba; Billingsley, Peter F.; et al. (Frontiers in Immunology, 2022)
Ionizing radiation (UV, X-ray and ɣ) administered at an appropriate dose to pathogenic organisms can prevent replication while preserving metabolic activity. We have established the GMP process for attenuation by ionizing radiation of the Plasmodium falciparum (Pf) sporozoites (SPZ) in Sanaria® PfSPZ Vaccine, a protective vaccine against malaria. Mosquitoes raised and infected aseptically with Pf were transferred into infected mosquito transport containers (IMTC) and ɣ-irradiated using a 60Co source. PfSPZ were then extracted, purified, vialed, and cryopreserved. To establish the appropriate radiation conditions, the irradiation field inside the IMTCs was mapped using radiochromic film and alanine transfer dosimeters. Dosimeters were irradiated for times calculated to provide 120-170 Gy at the minimum dose location inside the IMTC and regression analysis was used to determine the time required to achieve a lower 95% confidence interval for 150 Gy. A formula incorporating the half-life of 60Co was then used to construct tables of irradiation times for each calendar day. From the mapping studies, formulae were derived to estimate the minimum and maximum doses of irradiation received inside the IMTC from a reference dosimeter mounted on the outside wall. For PfSPZ Vaccine manufacture a dose of 150 Gy was targeted for each irradiation event, a dose known to completely attenuate PfSPZ. The reference dosimeters were processed by the National Institute of Standards and Technology. There have been 587 irradiation events to produce PfSPZ Vaccine during 13 years which generated multiple lots released for pre-clinical studies and clinical trials. The estimated doses at the minimum dose location (mean 154.3 ± 1.77 Gy; range 150.0-159.3 Gy), and maximum dose location (mean 166.3 ± 3.65 Gy, range 155.7 to 175.3 Gy), in IMTCs were normally distributed. Overall dose uniformity was 1.078 ± 0.012. There was no siginifcant change in measured dose over 13 years. As of January 2022, 21 clinical trials of PfSPZ Vaccine have been conducted, with 1,740 volunteers aged 5 months to 61 years receiving 5,648 doses of PfSPZ Vaccine totalling >5.3 billion PfSPZ administered. There have been no breakthrough infections, confirming the consistency and robustness of the radiation attenuation process.